1993
DOI: 10.1182/blood.v81.5.1137.bloodjournal8151137
|View full text |Cite
|
Sign up to set email alerts
|

The place of high-dose BEAM therapy and autologous bone marrow transplantation in poor-risk Hodgkin's disease. A single-center eight- year study of 155 patients

Abstract: Although high-dose chemotherapy and autologous bone marrow transplantation (ABMT) are increasingly being used for the treatment of relapsed and resistant Hodgkin's disease, there have been few large, single-center studies reported with adequate follow-up to allow full evaluation of this therapeutic modality. We present 155 poor-risk Hodgkin's disease patients who received high-dose BEAM (BCNU, etoposide, cytosine arabinoside, and melphalan) chemotherapy and ABMT who have been studied over a period of 8 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
67
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 0 publications
9
67
0
Order By: Relevance
“…Even if the number of cases with refractory disease is relatively small, our data (5-year EFS, 26.1 Ϯ 9.26%) confirm the poor prognosis of this subset of patients. Similar results have been reported by the London group, 4 with a 33% PFS rate at 6 years (95%, confidence interval 21-50%) in a population of 46 patients with primary refractory HD treated with the BEAM regimen. The team from Stanford University recently reported results with high-dose therapy and autografting that appeared to be better than ours in patients with refractory HD, with 5year EFS rate from 48 to 53%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Even if the number of cases with refractory disease is relatively small, our data (5-year EFS, 26.1 Ϯ 9.26%) confirm the poor prognosis of this subset of patients. Similar results have been reported by the London group, 4 with a 33% PFS rate at 6 years (95%, confidence interval 21-50%) in a population of 46 patients with primary refractory HD treated with the BEAM regimen. The team from Stanford University recently reported results with high-dose therapy and autografting that appeared to be better than ours in patients with refractory HD, with 5year EFS rate from 48 to 53%.…”
Section: Discussionsupporting
confidence: 87%
“…With the same median time interval from diagnosis to ASCT of 28 months, the risk appears to be lower in Chopra's series, who reported only two cases of MDS out of 155 transplantations after the BEAM conditioning regimen in a single center 8-year study. 4 Darrington et al 25 reported an estimated cumulative incidence of MDS and secondary leukemia of 4% at 5 years in a one-center study of 511 ASCT for lymphoid malignancies, and they estimated that the probability of MDS or leukemia among patients with HD alive at 5 years was 11%. Post-autologous Table 3 Results of prospective and randomized trials testing chemotherapy or CMT in advanced HD Research group (Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Josting et al found the 5-year OS of patients with primary progressive disease was 26% for all patients compared to 43% of those treated with HDT (32). HDT with autologous stem cell transplantation has shown promising results in a number of studies, with better reported disease free survival rates of 31-42% (33,34), and this approach is now often adopted for those who are chemo-responsive, although further confirmatory trials are needed. It is clear that the adolescents had more early deaths, most of which were secondary to refractory or primary progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…However some groups report similar outcomes comparing these groups (Smith et al , 2011). Of note, most of these analyses are performed once patients have reached HDT/ASCR (Chopra et al , 1993; Nademanee et al , 1995; Horning et al , 1997; Sweetenham et al , 1999; Majhail et al , 2006) rather than by intention‐to‐treat (ITT) (Ferme et al , 2002), which limits the true extent of conclusions that can be drawn on the relative risk of ER/FTF compared to the LR patients, by selecting the good‐risk group of patients who have responded to salvage treatment and reached HDT/ASCR.…”
mentioning
confidence: 99%